Mitigating Violence in Schools: The Role of the Violence Prevention and Handling Team (TPPK) at UPT SMA Model Negeri 5 Enrekang - Ihda, Hijriani; Jumadi, Jumadi; Idrus, Idham Irwansyah; Ridha, Rasyid; Najamuddin, Najamuddin (Tamaddun Life, 2025)
Violence in school settings presents a critical challenge that undermines both academic achievement and personal development. This study examines various forms of violence ranging from verbal aggression (bullying, name-calling, and rumor-spreading) to physical confrontations (individual fights and brawls) at UPT SMA Model Negeri 5 Enrekang, a senior high school in Enrekang Regency, Indonesia. Employing a qualitative research design, data were collected through in-depth interviews, observations, and document analysis with a diverse group of participants, including students, teachers, and members of the Violence Prevention and Handling Team (TPPK). The findings reveal that verbal violence often serves as a precursor to physical aggression, with minor acts of teasing escalating into serious conflicts when coupled with interpersonal tension, unresolved personal grievances, and power imbalances among students. The TPPK plays a pivotal role in mitigating these incidents through prompt intervention, counseling, and the implementation of preventive measures. However, the study suggests that school-based efforts alone are insufficient. Comprehensive strategies, including enhanced teacher training, increased parental engagement, and robust community collaboration, are essential for fostering a safe and conducive learning environment. These results have significant implications for educational policy and practice, highlighting the need for holistic, proactive approaches to reduce violence in schools. Future research should focus on the longitudinal effects of these interventions and consider broader contextual factors influencing school violence.